Investigation of mechanical properties of short- and long-term aged asphaltite modified asphalt mixtures - Yılmaz, Mehmet; Kök, Baha Vural; Kuloğlu, Necati (My University, 2013)
In this study, the effects of asphaltite and long-term aging on the mechanical properties of hot mix asphalt were investigated. The asphaltite entrained as filler at five different proportions into the hot mix asphalt samples and the obtained results were compared against the control mixtures. The pure and asphaltite containing compacted mixtures were exposed to long-term aging in an oven. Marshall stability, resistance to moisture-induced damage and resistance to crack propagation tests in accordance with the principles of elastic-plastic fracture as well as linear-elastic fracture mechanics were carried out on the mixtures. It was determined that the optimal proportion of asphaltite usage as filler with respect to volumetric design is 3% by weight. The test results demonstrated that asphaltite use enhances the resistance against permanent deformation, moisture-induced damage and crack propagation especially at normal temperatures, albeit at the cost of causing the hot mix asphalt to exhibit a more brittle behavior. The use of asphaltite would be suggested in order to reduce the long-term effects of aging in general specifically on account of the results of the stability, moisture-induced damage and fracture toughness tests.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot mix asphalt; Mechanical properties; Asphaltite; Long-term aging; Fracture